Rheology Behaviours of Miscible Amorphous Poly(3-hydroxybutyrate)/Poly(ethylene oxide)/Poly(p-vinylphenol) Blends - Jin, Q.Q.; Chen, Q.; Wang, K.X.; Ding, G.Z.; Liu, J.P. (Asian Journal of Chemistry, 2016)
Much attention has been focused on the development and investigation of polymer blends in previous years. The miscibility and rheology behaviours of poly(3-hydroxybutyrate) (PHB), poly(ethylene oxide) (PEO) and poly(p-vinylphenol) (PVPh) blends are studied in this work. The linear dynamic viscoelasticity of PHB/PEO/PVPh blends with miscible amorphous composition are investigated by the oscillatory shear measurements. It shows that time-temperature superposition principle (TTS) is applicable for blends. The Han plot (log G' vs. log G") is temperature independent, however, the slopes in the terminal region are much less than 2 and become smaller with the addition of poly(ethylene oxide) content. It is considered that this phenomenon might be resulted from the presence of whole hydrogen bonding change (the self-associated interaction and the hydrogen bonding with hydroxyl group, ether group and ester group) in the blends. This conclusion is supported by the Fourier transform infrared spectroscopy analysis.